The strawberry generation: a sweet but fragile challenge for Malaysia’s future workforce - Kasim, Syazliana (Universiti Teknologi MARA Cawangan Negeri Sembilan Kampus Rembau, 2025)
The term “strawberry generation,” originating from Taiwan, is often used to describe Gen Z youths as sensitive and less resilient, shaped by a comfortable, technology-driven upbringing. In Malaysia, this label raises questions about fairness and its implications for future human capital, as while these individuals are digitally fluent, socially aware, and expressive, critics argue they may struggle with pressure and real-world challenges.